Optimalisasi Manajemen Stres sebagai Upaya Peningkatan Kinerja Perawat di Rumah Sakit - Rohita, Tita; Nurkholik , Dedeng; lestari, Intan; Nuralam, Deni; Indriyani, Indriyani; Lesmana, Indra (Yayasan Inspirasi El Burhani, 2024)
Introduction High stress among nurses can affect the performance and quality of services in hospitals. Effective stress management is the key to improving nurse performance and the quality of health services. Therefore, optimizing stress management is an important focus in efforts to improve nurse performance. The aim of this service aims to optimize stress management strategies and evaluate their impact on improving the performance of nurses in hospitals. The methods used include stress management training for nurses in hospital inpatient rooms. Data was collected through surveys, interviews, and observations before and after strategy implementation. Results Nurse performance scores and stress levels were measured using a questionnaire. Before implementing the strategy, the average nurse performance score was 3.5 with an average stress level of 4.2. After implementing the stress management strategy, the performance score increased to 4.1 and the stress level decreased to 3.2, indicating that the stress management strategy was successful in improving nurse performance and reducing stress levels. Optimizing stress management is effective in improving nurse performance and reducing stress levels in hospitals. This program makes a positive contribution to the quality of health services and the work welfare of nurses. Recommendations include continued implementation of these strategies and provision of additional support for nurses.